Assessing the world trade organization fit for purpose? : world trade forum - Elsig, Manfred; Hoekman, Bernard M. 1959; Pauwelyn, Joost; World Trade Forum (2015 Bern, Switzerland). (Cambridge, United Kingdom Cambridge University Press, 2017)
"With chapters written by scholars who have closely observed the development of the WTO in recent years, this book presents the state of the art in thinking about WTO performance. It also considers important issues such as the origins of the multilateral system, the accession process and the WTO's interaction with other international organisations."--Provided by publisher.
Part I. Introduction and Setting the Stage: 1. Introduction Manfred Elsig, Bernard Hoekman and Joost Pauwelyn -- 2. Thinking about the performance of the World Trade Organization: a discussion across disciplines Manfred Elsig, Bernard Hoekman and Joost Pauwelyn -- Part II. New Insight from the Early Times: 3. The GATT's starting point: tariff levels circa 1947 Chad P. Bown and Douglas A. Irwin -- 4. Negotiating in the early GATT: norms, rules and the US tariff schedule Judith Goldstein and Robert Gulotty -- Part III. General Trends and Patterns in WTO Dispute Settlement -- 5. Dispute settlement in the WTO: from a deliberately designed to a spontaneously grown order Frieder Roessler -- 6. About the melting of icebergs: political and economic determinants of dispute initiation and resolution in the WTO Dirk de Bievre, Arlo Poletti and Aydin Yildirim -- 7. The WTO dispute settlement system: consolidating success and confronting new challenges Giorgio Sacerdoti -- 8. Does trade comply? The economic effect(iveness) of the WTO dispute settlement process Soo Yeon Kim and Tobias Hofmann -- Part IV. Zooming in on Specific Debates -- 9. Twenty years of third party participation at the WTO: what have we learned? Krzysztof J. Pelc -- 10. Mind the gap: navigating between the WTO agreement and its accession protocols Julia Qin -- 11. The age of innocence - the evolution of the case-law of the WTO dispute settlement: subsidies as a case-study Luca Rubini -- 12. The presence of the World Trade Organization within preferential trade agreements Todd Allee and Manfred Elsig -- 13. The WTO and regional trading agreements: is it all over for multilateralism? L. Alan Winters -- 14. Performance and international organisations' borders: the case of the World Trade Organization Cedric Dupont and Manfred Elsig -- 15. The GATT/WTO system and national trade policies: which comes first? Joseph Michael Finger.
Includes index.
Keywords: World Trade Organization -- Congresses; International trade -- Congresses; Commercial policy -- Congresses